Antistreptolysin O titer in health and disease: levels and significance - Kotby, Alyaa Amal (PAGEPress Publications, 2012)
Over diagnosis of acute rheumatic fever (ARF) based on a raised antistreptolysin O titer (ASOT) is not uncommon in endemic areas. In this study, 660 children (aged 9.2 ±1.7 years) were recruited consecutively and classified as: G1 (control group, n=200 healthy children), G2 (n=20 with ARF 1(st) attack), G3 (n=40 with recurrent ARF), G4 (n=100 with rheumatic heart disease (RHD) on long acting penicillin (LAP)), G5 (n=100 with acute follicular tonsillitis), and G6 (n=200 healthy children with history of repeated follicular tonsillitis more than three times a year). Serum ASOT was measured by latex agglutination. Upper limit of normal (ULN) ASOT (80(th) percentile) was 400 IU in G1, 200 IU in G4, and 1600 IU in G6. Significantly high levels were seen in ARF 1st attack when compared to groups 1 and 5 (P<0.001 and P<0.05, respectively). ASOT was significantly high in children over ten years of age, during winter and in those with acute rheumatic carditis. ASOT showed significant direct correlation with the number of attacks of tonsillitis (P<0.05). Egyptian children have high ULN ASOT reaching 400 IU. This has to be taken into consideration when interpreting its values in suspected ARF. A rise in ASOT is less prominent in recurrent ARF compared to 1st attack, and acute and recurrent tonsillitis. Basal levels of ASOT increase with age but the pattern of increase during infection is not age dependent.